Community Empowerment in the Development of Local Home Industrial Businesses Based in Licin Village, Licin District, Banyuwangi Regency - Didiek Tranggono; Ririn Puspita Tutiasri (Nusantara Science and Technology Proceedings)
Banyuwangi has a lot of natural potential, which if it gets an intensive assistance from certain parties: government and related agencies, and higher education through research and community service, then it is possible that it will be better able to change progress more powerful in the villages. One of the examples is the variety of potential that exists in Licin, where most of the communities are farmers. Aside from farming cassava and corn, many farmers are growing oyster mushrooms, and also many other natural potentials. If these potentials get even more serious attention then it is possible that it will be able to change the pattern of community life that is promising in improving the welfare of the community's family, especially in the Licin. However, due to the lack of the quality of human resources, it causes various obstacles in optimizing all the potential that exists in this village. These obstacles include, among others, inadequate social, economic, and cultural problems in the community. Licin village, Banyuwangi is one of the national priority villages that need to get more serious attention from various parties, in an effort to improve the welfare of the community. The purpose of the thematic community service program in the first year is to do potentials and problems mapping in Licin village. Program planning, home industry business management, and action plans making to be implemented in the second year. Seeing the potential of the village, the problems faced by the community, and how the society overcome the problems, it is necessary to empower and develop the community in the context of what efforts should be done based on the potential that exists in the village. Whereas the target of this thematic community service program is to utilize and optimize the potential in their village, to make good use of it, which in turn can increase income and family welfare. The results will be achieved after mapping the potentials and problems of the community based on the existing potential. In the future, it is necessary to do more intensive training and assistance in making shredded oyster mushrooms, so that it is expected to increase the income of community families in Licin.